Apollo 11 rockets to first moon landing - Green, Carl R. (Space flight adventures and disasters, 2004)
Discusses the events of the 1969 Apollo 11 mission, Neil Armstrong's famous moon landing, and provides Internet links to related Web sites, source documents, and photographs.